Ignorance is bliss: Voter education and alignment in distributive politics - Federico Boffa; Francisco Cavalcanti; Amedeo Piolatto (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2021)
Central-government politicians channel resources to sub-national entities for political gains. We show formally that the central politicians' allocation decision has two drivers: political alignment (between central and local politicians) and the level of local political accountability. However, drivers count one at a time: alignment matters before local elections, while local political accountability matters before central elections. We then perform a test of our model using Brazilian data, which corroborates our results. Furthermore, we show and explain why political accountability becomes a curse: better-educated districts receive fewer transfers in equilibrium.
Keywords: D72; H11; H7; 330; Federalism; Distributive Politics; Partisan Alignment; Voters' Education; Political Accountability; Brazil